Analisis Tingkat Kepercayaan Pada Nasabah Bank Umum Pasca Kasus Century - Yuliza Yuliza; Rain Linda Sari (Ekonomi dan Keuangan, 2013)
This research aims to determine whether or not the average difference before and after the Century Bank Case. The research method in this thesis used descriptive research method. Type of data used is secondary data. Secondary data obtained by requesting data directlyinto Indonesian Bank. Data Collected were analyzed by the method of data analysis that test and then proceed with the normal distribution using paired sample test. Analysis shows that not all commerial bank affect customer confidence in the Century Bank case. The state banks only Mandiri bank that shows the influence of reduced customer confidence in Century Bank case post that looks at variable demand and time deposits, whilein private banks only Ekonomi Bank that looks at the variable savings.Keywords : Customer Confidence, Century Bank, Demand Deposits, Savings and Time Deposits